Stereotactic Body Radiation Therapy for Liver Metastases from Colorectal Cancer: Analysis of Safety, Feasibility, and Early Outcomes - Kress, Marie-Adele S.; Collins, Brian T.; Collins, Sean; Dritschilo, Anatoly; Gagnon, Gregory; Unger, Keith (Frontiers in Oncology, 2012)
Introduction: Colorectal cancer (CRC) is the 3rd leading cause of cancer-related death in the U.S. Many patients with CRC develop hepatic metastases as the sole site of metastases. Historical treatment options were limited to resection or conventional radiation therapy. Stereotactic body radiation therapy (SBRT) has emerged as a rational treatment approach. This study reviews our experience with SBRT for patients with liver metastases from CRC. Material and Methods: Fourteen histologically confirmed hepatic CRC metastases in 11 consecutive patients were identified between November, 2004 and June, 2009 at Georgetown University. All patients underwent CT-based treatment planning; a few also had MRI or PET/CT. All patients had fiducial markers placed under CT guidance and were treated using the CyberKnife system. Treatment response and toxicities were examined; survival and local control were evaluated. Results: Most patients were treated to a single hepatic lesion (n=8), with a few treated to 2 lesions (n=3). Median treatment volume was 99.7 cm3, and lesions were treated to a median BED10 of 49.7 Gy (range: 28 – 100.8 Gy). Median follow-up was 21 months; median survival was 16.1 months, with 2-year actuarial survival of 25.7%. One-year local control was 72%. Among patients with post-treatment imaging, 8 had stable disease (80%) and 2 had progressive disease (20%) at first follow-up. The most common grade 1-2 acute toxicities included nausea and alterations in liver function tests; there was one grade 3 toxicity (elevated bilirubin), and no grade 4-5 toxicities. Discussion: SBRT is safe and feasible for the treatment of limited hepatic metastases from CRC. Our results compare favorably with outcomes from previous studies of SBRT. Further studies are needed to better define patient eligibility, study the role of combined modality treatment, optimize treatment parameters, and characterize quality of life after treatment.